Peran Faktor-Faktor Keuangan dalam Mendorong Agresivitas Pajak : Literature review - Yulia Indah Prastika; Sofie Yunida Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the role of financial factors in encouraging corporate tax aggressiveness using a literature review approach. Taxes are a major source of government revenue, making tax aggressiveness an important issue in accounting and taxation research. This study applies the Systematic Literature review (SLR) method by examining previous studies related to leverage, capital intensity, and profitability in influencing tax aggressiveness. Data were obtained from scientific articles indexed in academic databases such as Sinta 2 and Scopus published between 2020 and 2024. The results show that leverage in several studies has a positive effect on tax aggressiveness because interest expenses can reduce taxable income. Capital intensity shows mixed findings, including positive, negative, and insignificant effects on tax aggressiveness. Profitability also presents inconsistent results across studies. Overall, financial factors have varying roles in influencing corporate tax aggressiveness, and factors such as leverage, capital intensity, and profitability play a very important role in determining how much a company engages in tax avoidance practices.